PENYULUHAN MENGENAI RABIES PADA SISWA SLTP KERTHA WISATA DI DESA TARO KECAMATAN TEGALALANG, KABUPATEN GIANYAR - Sari, Ayu Kartika; Sutarsa, I N.; Aryani, P.; Ani, L. Seri; Dharmadi, M. (Buletin Udayana Mengabdi; Vol 11 No 1 (2012): Jurnal Udayana Mengabdi, 2012)
The incidence of dog bite in Gianyar regency is tending to be increased for last two months. Based on the field observation and interview with some people in Taro Village, we may conclude that Taro Village has the high of dog population which are distributed in all area. Most of the people living there are keeping the dogs free. This is an indication the low level of community awareness regarding the risk of rabies transmission. This program is aimed to increase the level of knowledge and to increase the awareness of the community in Taro, especially high school youth regarding rabies transmission and an effort to prevent its transmission. Furthermore, they are expecting to be conducted the prevention activity for both family and community level. This program was conducted on Saturday, 18th of September 2010 with total participants were 56 students. They seemed very enthusiastic during the education program, especially when they watched the movie of rabies. Pre and post test were applied to evaluate the program effectiveness in increasing the level of knowledge of the students. The result shows that their level of knowledge are increased (21,4% participants had a good knowledge at pre test and 98,2% participants at post test). We may conclude that the program is well accepted and effective to improve the level of knowledge of the students.